Elevated risk of infectious diseases in adulthood after prenatal or early postnatal exposure to the Great Chinese Famine - Qi Li; Philip A. Collender; Hailan Yu; Kristin N. Nelson; Jon Zelner; Xinqiang Wang; Xiaolu Wang; Jiayi Tang; Leonardo Martinez; Justin V. Remais; Changhong Yang; Qu Cheng (Proceedings of the National Academy of Sciences, 2025)
Although prenatal exposure to famine is known to increase the risk of various noncommunicable conditions, its effects on infectious diseases remain poorly understood. We examined the effect of prenatal exposure to the Great Chinese Famine on risks for 11 notifiable infectious diseases in two consecutive generations through the analysis of >4.4 million surveillance records in Sichuan Province, China. Using an approach combining cohort models with counterfactual effect imputation, we estimated the ratio of observed to expected incidence rates (incidence rate ratio, IRR) in the absence of famine among both the directly affected birth cohort (F1) and their possible offspring (F2). We further examined whether there was a dose–response relationship between famine severity and infectious disease outcomes using meta-regression at the prefecture level. We found that the risk of acquiring any of the 11 infectious diseases studied increased significantly among both the F1 (IRR: 1.13, 95% CI: 1.04 to 1.21) and the F2 cohort (IRR: 1.08, 95% CI: 1.00 to 1.15). IRRs for the F1 generation were higher in prefectures that experienced more severe famine, with one interquartile range increase in famine severity associated with a 3.95% (95% CI: 1.87 to 6.05%) increase in F1 IRR. Positive associations of varying magnitudes were estimated between increased risks in the F1 cohort and famine intensity for most individual diseases. Prenatal exposure to famine may have long-term and potential intergenerational impacts on the risk of a broad range of infectious diseases. Ensuring adequate prenatal nutrition may be crucial in reducing the burden of infectious diseases across generations.